2001
DOI: 10.1029/2001gl013152
|View full text |Cite
|
Sign up to set email alerts
|

T‐waves excited by S‐waves and oscillated within the ocean above the Southeastern Taiwan Forearc

Abstract: Abstract. The generation processes of T-waves were investigated from seismograms produced by a local intermediate-depth earthquake and recorded at one shortperiod station in Taiwan. The first group of T-phases arrived 44 seconds after the S-phases, while the following 2 groups consistently had the same travel-time difference of about 88 seconds each. Analyses of the ray paths and travel-times of these phases show that the T-waves were converted from the S-waves and oscillated within the ocean above the forearc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Note the relatively early arrivals of the predicted T-waves can be considered as part of T-wave segments are propagating inside solid earth and the seismic wave propagation in faster velocity than acoustic wave at sea. bathymetry (the ocean-water interface) in trapping acoustic energy inside the low-velocity waveguide (SOFAR channel) is a fundamental aspect of the conversion of seismic energy into acoustic waves at the event source location, the T-waves themselves, however, are considered to represent acoustic energy that was converted from the P-or Lg-phases originating from shallow seismic events (Koyanagi et al 1995;Talandier and Okal 1998), or alternatively, from the S-waves originating from deep earthquakes (Okal and Talandier 1997;Lin 2001). Early named this model as the downslope conversion model, it was originally proposed to explain many attributes of the observed T-waves, and this model proved to be quite adequate in doing so (Officer 1958;Johnson et al 1963).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note the relatively early arrivals of the predicted T-waves can be considered as part of T-wave segments are propagating inside solid earth and the seismic wave propagation in faster velocity than acoustic wave at sea. bathymetry (the ocean-water interface) in trapping acoustic energy inside the low-velocity waveguide (SOFAR channel) is a fundamental aspect of the conversion of seismic energy into acoustic waves at the event source location, the T-waves themselves, however, are considered to represent acoustic energy that was converted from the P-or Lg-phases originating from shallow seismic events (Koyanagi et al 1995;Talandier and Okal 1998), or alternatively, from the S-waves originating from deep earthquakes (Okal and Talandier 1997;Lin 2001). Early named this model as the downslope conversion model, it was originally proposed to explain many attributes of the observed T-waves, and this model proved to be quite adequate in doing so (Officer 1958;Johnson et al 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The 'T' in T-phase (and T-wave) denotes 'tertiary' because these waves are the third type to arrive, after P-(primary) and S-(secondary) waves which propagate instead through the Earth's crust; as a rule, Tphases are recorded at sea using hydrophones. However, the seismic conversion wave generated by a T-phase that strikes an island or continental shore can also be recorded by a seismometer on land (Shurbet 1955;Galanopoulos and Drakopoulos 1974;Lin 2001;Huang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two different mechanisms have been identified to explain the T-wave coupling. 28 The first one is ''slope conversion,'' which is controlled by seafloor slope. 29,30 The second mechanism is scattering of energy into the sound channel at bathymetric promontories in close proximity to the source region.…”
Section: Influence Of Parametric Mode Conversion On Seaõ Bottom Comentioning
confidence: 99%
“…In recent years, several studies have reported T-phase observations in the Taiwan area using modern digital network observations (Chiu 1993;Lin 2001;Tu 2008;Wei 2010). Chiu (1993) reported the dominate frequencies of T phases recorded at Lu-Tao within 5 to 10 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Chiu (1993) reported the dominate frequencies of T phases recorded at Lu-Tao within 5 to 10 Hz. Both Lin (2001) and Tu (2008) reported the multiple path effects of T phase from eastern Taiwan offshore events. Wei (2010) reported T phases recorded in Taiwan inland stations from teleseismic events.…”
Section: Introductionmentioning
confidence: 99%